Renewable fuels - Kant, Rajni; Kant, Keshav (Boca Raton CRC Press, 2024)
Renewable fuels, in the present times, have become important to curb the emission of greenhouse gases, which are causing damage to the environment and leading to climatic changes. Ideally, their utilization can be a zero-carbon operation. Planting suitable trees on all wastelands and agroforestry on a large scale can fulfill the needs of timber, fuel, fruits, etc. All kinds of lignocellulosic biomass can be converted by several methods to use liquid fuels like alcohols, biodiesel, methane, renewable diesel, and renewable gasoline. Hydrogen can be used as a renewable fuel because of its desirable characteristics and properties for its use as a green fuel.
Keywords: Built environment; Engineering and technology